Pharmaceutical marketing and patient trust: How do doctor-targeted campaigns affect patients? - Marta Makowska; Akihiko Ozaki; Piotr Ozieranski (PLoS ONE, 2026)
Background In the context of pervasive pharmaceutical marketing directed at doctors, it is crucial to understand whether patients notice these activities and, if so, what impact this may have on trust in doctor-patient relationships. Methods The study was conducted through an online survey with 1,057 Polish participants. A quota sample, reflecting the Polish population in terms of specific socio-demographic characteristics, was chosen from an internet panel. Results The average trust in physicians among Poles, on a 10-point scale, was 6.3 (SD = 2.1), while the average trust in pharmaceutical companies was lower, at 5.0 (SD = 2.3). The results indicate that 83.4% of respondents noticed signs of pharmaceutical marketing directed at doctors, with 5.5% experiencing all six types of marketing practices addressed in the study. Seeing a company logo in the doctor’s office, encountering a pharmaceutical sales representative (PSR), and experiencing PSR-related longer waits were each associated with lower trust in physicians (t = −2.2, −2.3, −2.9; p = .028,.019,.004; d = −.136, − .148, − .188, respectively) and in pharmaceutical companies (t = −2.7, −3.1, −2.3; p = .008,.002,.021; d = −.166, − .202, − .151, respectively). Receiving a free drug sample was linked to slightly higher trust in physicians (t = 2.2, p = .028, d = .16) and showed no effect on trust in companies (p = .558). Most pairwise correlations among patient-encounter pharmaceutical marketing situations were weak, even when they reached statistical significance; the only strong association was between encountering a PSR in a medical facility and reporting PSR-related longer wait times (r = .69, p < .001). Conclusion Physicians and pharmaceutical companies must acknowledge that their marketing relationships can influence patient trust and should carefully assess the consequences of their collaboration on the public’s perception of medicine and public health.